2018
DOI: 10.1111/idh.12337
|View full text |Cite
|
Sign up to set email alerts
|

High birthweight is associated with increased prevalence of dental caries in Japanese children

Abstract: Our findings indicate that high birthweight might increase the likelihood of dental caries in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 23 publications
0
16
0
1
Order By: Relevance
“…The authors included 14 studies [12][13][14][15][16][17][18][19][20][21][22][23][24][25] covering 210,691 children in this review, and the main characteristics are shown in Table 1.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors included 14 studies [12][13][14][15][16][17][18][19][20][21][22][23][24][25] covering 210,691 children in this review, and the main characteristics are shown in Table 1.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Three studies were based on prospective birth cohorts, [12][13][14] and two used population registers. 24,25 Seven were cross-sectional trials, [15][16][17][18][19][20][21] and two employed a case-control design. 22,23 The number of participating children per study ranged from 128 to 117,175 with median value of 1,019.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have addressed the association between dental caries and preterm birth and/or LBW, but the findings remain unclear due to methodological differences and conflicting conclusions . Therefore, the aim of the present systematic review and meta‐analysis was to evaluate the prevalence of dental caries (outcome) in preschool children (patients) born preterm and/or with a LBW (exposure) compared to children born full term and/or with a normal birth weight (NBW) (comparison).…”
Section: Introductionmentioning
confidence: 99%
“…The influence of prenatal period, preterm birth, state of health and parents' age has already been proved (3). Several studies have been recently carried out to reveal the effects of the pathological course of pregnancy on dental health (4).…”
Section: Introductionmentioning
confidence: 99%